Direct drive or slider-crank? Comparing motor-actuated flapping-wing micro aerial vehicles - Moonsoo Park; Ali Abolfathi (Drone Systems and Applications, 2024)
For flapping-wing micro aerial vehicles, the common approach to converting the rotational motion of a DC motor to the reciprocal flapping motion is using a slider-crank mechanism. However, frictional losses in sliders and rotational joints can hinder the performance of such a system. An alternative is a direct drive system where the wings are directly connected to a DC motor that has been driven by an AC signal. These two approaches are compared in this paper, to evaluate their performances and assess which one provides a better solution for flapping-wing micro drones. The electromechanical model of the two systems is used in this paper to compare their performances. System parameters for both types of drones were derived through a multi-variable optimisation process using the same DC motor. The comparisons are made in terms of input power requirement, aerodynamic power, system efficiency, and lift. The direct drive model can generate about 16% higher average lift at 5 V with 50% lower input electrical power. It has 29% larger aerodynamic power and the system efficiency is 16.0% higher than that of the slider-crank model.